2017
DOI: 10.3892/ol.2017.6187
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib does not impair natural killer cell function in patients with renal cell carcinoma

Abstract: Abstract. Although the available treatment options have expanded, the survival of patients with metastatic renal cell carcinoma (RCC) remains poor. As patients with RCC lack responsiveness to chemotherapy or radiation, therapeutic options predominantly include surgical interventions and immunomodulatory approaches, including the administration of tyrosine kinase inhibitors (TKIs) such as sunitinib. Natural killer (NK) cells have been reported to be key players in TKI-mediated off-target effects on the immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Reassuringly, most designated neutrophils, macrophages, and eosinophils were found in the myeloid pool and most designated T cells, NK cells, and B cells were found in the lymphoid pool. Moreover, most lymphoid cells were designated as T cells, which is consistent with previous reports of counts of lymphoid cells in RCC (32). Admittedly, technical issues may exist that led to some apparent artefacts, such as assignment of some B cells in the myeloid pool.…”
Section: Resultssupporting
confidence: 90%
“…Reassuringly, most designated neutrophils, macrophages, and eosinophils were found in the myeloid pool and most designated T cells, NK cells, and B cells were found in the lymphoid pool. Moreover, most lymphoid cells were designated as T cells, which is consistent with previous reports of counts of lymphoid cells in RCC (32). Admittedly, technical issues may exist that led to some apparent artefacts, such as assignment of some B cells in the myeloid pool.…”
Section: Resultssupporting
confidence: 90%
“…For example, resting and IL-2 activated NK cells exhibited less degranulation and cytokine production when exposed to pharmacological doses of sorafenib, but not sunitinib, in a mechanism involving impaired PI3K and ERK phosphorylation [164]. Other studies have also shown that sunitinib does not impair NK cell function in patients with RCC [165]. On the other hand, sunitinib has been found to induce the expression of MICA, MICB, and ULBP1-3, all of them ligands of the activating NKG2D receptor, on nasopharyngeal cancer cell lines that lead to an increase in their susceptibility to NK cell-mediated cytoxicity [166].…”
Section: Nk Cells and Renal Cell Carcinomamentioning
confidence: 97%